2023
DOI: 10.1080/22423982.2023.2178068
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical features of heart failure in Greenland

Abstract: Heart Failure (HF) constitutes a significant burden for healthcare around the world. In Greenland, risk factors like smoking, diabetes, and obesity are prevalent. Yet, the prevalence of HF remains unexplored. This register-based cross-sectional study uses data from the national medical record in Greenland to estimate the age- and gender-specific prevalence of HF and to describe the characteristics of patients with HF in Greenland. A total of 507 patients (26% women) with a mean age of 65 years were included ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“… 37 Similarly, heart failure was reported by 1%, which corresponds to the prevalence described by Larsen et al. in 2023, 38 and the self-reported prevalence of ischemic heart disease is similar to that found by Jørgensen et al. in a study including 1316 Greenlandic Inuit participants aged ≥ 18 years.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“… 37 Similarly, heart failure was reported by 1%, which corresponds to the prevalence described by Larsen et al. in 2023, 38 and the self-reported prevalence of ischemic heart disease is similar to that found by Jørgensen et al. in a study including 1316 Greenlandic Inuit participants aged ≥ 18 years.…”
Section: Discussionsupporting
confidence: 78%
“… 43 Our study did not include genetic data, but a well established finding is that the Greenlandic Inuit population has genetic traits that increase the risk of type 2 diabetes, and higher levels of cholesterol and triglycerides. 44 , 45 In addition, a study from Canada found a higher rate of congenital QT syndrome among some First Nations participants, 46 and the Inuit population in Greenland has a higher rate of congenital heart disease and nonischemic heart failure than that among the non-Inuit population, 38 , 47 , 48 all of which can create a predisposition for AF. Some ethnic minorities may have an increased susceptibility to early-onset AF due to genetic variants, 49 and we found an AF prevalence of 7% among the youngest agegroup included in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of diagnosed diabetes in the Greenlandic background population aged 20 years or older was 3.7% in 2020 [ 18 ]. Larsen et al estimated the prevalence of HF to be 1.1% in the Greenlandic population aged 16 years or above [ 38 ].…”
Section: Discussionmentioning
confidence: 99%